FACTORS HINDERING THE ACHIEVEMENT OF ENGLISH COMMUNICATIVE COMPETENCE - Menggo, Sebastianus; Suparwa, I Nyoman; Astawa, I Gede (Aksara, 2019)
English communicative competence is one of the prime preferences for learners in this current century, including tourism academy students. As the consequence, learners are equipped by relevant skills including how to articulate English communicative competence insight effectively. Learners are encouraged to fulfill the of micro and macro components of English communicative competence and minimize the factors hindered to be a competent English speaker. The aims of this research were to analyze the factors hindering communicative competence and disclose the micro and macro component problems of English communicative competence at the fourth semester of hotel department students enrolled in three-year diploma program in Denpasar tourism academy. This was descriptive-quantitative study and involved 30 students and one English lecturer as respondents at this college. Data were collected through in-depth interview, questionnaire, field observation, and students’ English communicative competence document. Then, data were analysed by using software program, Excel Chart Data Series. The result indicates that internal factors were more affecting than external factors and micro components were more complicated than macro components in the students’ English communicative competence.